The Role Of Public Business Credit Financing By Financial Institutions On The Development Of MSME - Ni Luh Putu Ratna Wahyu Lestari; Ni Made Rai JUNIARIANI (International Journal of Environmental, Sustainability, and Social Science, 2021)
The Role of General Business Credit Financing by Financial Institutions in UMKM Development. Bank Indonesia Regulation No.14 / 22 / PBI / 2012 shows the government's attention to the KUR capital policy for MSMEs. However, the financing obtained from financing institutions may not be used optimally by MSMEs to run and develop their businesses. The role of financial institutions is still needed, apart from being a means of generating funds, also as a business facilitator, for example in the fields of management, markets and marketing, as well as finance as a means of providing funds will be easier to do when compared to the role of a facilitator for MSMEs. This research uses a qualitative approach. The research sample of 30 MSMEs in Bali Province received KUR funds from KSP Guna Prima Dana. The result of this research is that there is an increase in sales turnover, labor, and the number of customers after receiving KUR funds from KSP Guna Prima Dana. UMKM receiving KUR (People's Business Credit) financing from KSP Guna Prima Dana have experienced business development because the majority of sales turnover after receiving KUR funds is more than the sales turnover before receiving KUR funds.